A phase transition in a Widom–Rowlinson model with Curie–Weiss interaction. (12th July 2018) - Kozitsky, Yuri; Kozlovskii, Mykhailo
Abstract: An analog of the continuum Widom–Rowlinson model is introduced and studied. Its two-component version is a gas of point particles of types 0 and 1 placed in, in which like particles do not interact, whereas unlike particles contained in a vessel of volume repel each other with intensity . The one-component version is a gas of particles with multi-particle interactions of Curie–Weiss type. Its thermodynamic behavior is obtained by integrating out the coordinates of one of the components of the two-component version. In the grand canonical setting, a rigorous theory of phase transitions in this model is developed and discussed. In particular, for both versions, thermodynamic phases and phase diagrams are explicitly constructed and the equations of state are obtained and analyzed.